DEVELOP MAKASSAR LANGUAGE LEARNING MATERIALS FOR STUDENTS SMP/MTs IN SOUTH SULAWESI - Daeng, Kembong (Journal of Educational Science and Technology, 2015)
This research aims at yielding product of Makassar Language learning material for Junior High School or Islamic Junior High School students which is feasible in terms of context, language, and presentation. The research design employed refers to Four-D Research Development conducted by Thiagarajan (1974:5) through four stages, consisting ofwhich are (1) defining; (2) planning; (3) developing, and (4) disseminating. The research data is analyzed by using domain analysis technique with critical and reflective principles. This learning material is validated by the experts of language teaching, linguists and literature experts and has been tested to Makassar Language Teachers SMP/MTs in Makassar city as the field practitioners. The research finding describes that after this product is revised, the final assessment result of this product shows that this product is highly feasible (92%). Likewise, the test result of the practitioners (teachers) in the field is also in highly feasible category (96%). This research result shows that the developed product of Makassar language learning material can be used as one of Makassar language teaching resources in South SulawesiÂ Keywords: the development of learning materials, Makassar languages